MODEL SIMULASI LUAPAN BANJIR SUNGAI CILIWUNG DI WILAYAH KAMPUNG MELAYU–BUKIT DURI JAKARTA, INDONESIA - Fajar Yulianto; Muh Aris Marfai; - Parwati; - Suwarsono (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2009)
Jakarta is the biggest city in Indonesia located in the north-western of Java Island and between 5º59’–6º00’S and 106º30’–107º00’E. The total area is approximately 661,52 km2, and the population is more than 9 million in 2008. The occurrence of many flood in Jakarta had caused loss in properties, environmental degradations, and warsen communities health. A spatial approach model is applied to understand the effects of flood to land use in the research area. Objectives of the research are : 1) to create the hazard assessment model and 2) to calculate the impact of flood to the land use area. The methods consist of neighbourhood operation application development in the form of raster pixel calculation, in this case are the Digital Elevation Model values, by using mathematic calculation formula to assign the inundated area. Land uses, either the inundated or others, are the result of imagery data interpretations. Results of the research show that the simulation model represent the condition in the field when flood happened maximum scenario for inundation area of 2,00 m will affect to about 5,10 Ha (regular settlements); 80,82 Ha (irregular settlements); 2,22 Ha (open areas); 5,09 Ha (business areas); 40,39 Ha (office areas) and 18,83 (roads). Key words: Ciliwung flood, DEM, Iteration spatial model, GIS, Remote sensing